First-Trimester Threatened Abortion: Can Red Blood Cell Distribution Width-Standard Deviation Predict Miscarriage? - Sebnem Karagun; Yusuf Dal; Hamza Yildiz; Sefanur Gamze Karaca; Ahmet Zeki Nessar; Ayhan Coskun (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The objective of the study was to investigate the predictive value of red blood cell distribution width-standard deviation (RDW-SD) and another complete blood count (CBC) derived blood markers in patients presenting with threatened abortion concerning miscarriage.